What makes an employer? - Marco Caliendo; Frank M. Fossen; Alexander Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
As the policy debate on entrepreneurship increasingly centers on firm growth in terms of job creation, it is important to better understand which variables influence the first hiring decision and which ones influence the subsequent survival as an employer. Using the German Socioeconomic Panel (SOEP), we analyze what role individual characteristics of entrepreneurs play in sustainable job creation. While human and social capital variables positively influence the hiring decision and the survival as an employer in the same direction, we show that none of the personality traits affect the two outcomes in the same way. Some traits are only relevant for survival as an employer but do not influence the hiring decision, other traits even unfold a revolving door effect, in the sense that employers tend to fail due to the same characteristics that positively influenced their hiring decision.
Keywords: J22; J23; L26; 330; employer; entrepreneurship; business venturing; recruitment; firm growth; employment growth; personality